Manipulating cell behavior on a bacterial macro-polymer poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) via tuning the S-doped graphene ratio - Yildirim, Meryem Akkurt; Demirbilek, Murat; Gursu, Hurmus; Sahin, Yucel; Turkoglu, Nelisa (ELSEVIER, 2021)
Graphene is a material with various application potentials Graphene is a unique material with superiorities and has been applied in various fields for different purposes. Although studies on the utility of graphene oxide in the biomedical field are available, no evaluation has yet been done regarding the utility of sulfur doped (S-doped) graphene. The study focuses on the effect of blending the poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) membrane with sulfur heteroatom doped graphene and the evaluation of biological responses to Sdoped graphene/PHBHHx. PHBHHx membranes were blended with 1%, 0.5%, 0.1% (w/v) S-doped graphene. The morphological (SEM and Microscopy), chemical (FTIR and Raman spectroscopy), and surface area (BET) characterizations of S-doped graphene/PHBHHx membranes were performed. The presence of S groups on the surface was determined with the EDS results. Besides, the swelling profile and biodegradation tendency of the membranes were evaluated. The differentiation of protein adhesion, cell viability, cell adhesion, and cell proliferation by the increasing content of S-doped graphene was examined. The contact angle analysis revealed that modification of PHBHHx with S-doped Graphene reduced the free surface energy of PHBHHx membranes. Blending with S-doped Graphene has decreased the polarity of the PHBHHx membrane. The protein adsorption on the PHBHHx membrane was determined as 10.12 +/- 0.247 mg/ ml. Protein absorption on 1%, 0.5% and 0.1% S-doped graphene/PHBHHx membranes were determined as 11.34 +/- 0.551 mg/ml, 9.91 +/- 0.294 mg/ml and 9.48 +/- 0.093 mg/ml, respectively. The cell attachment to the surface decreased with the increasing amount of S-doped graphene, however, PHBHHx membranes with graphene did not affect cytotoxicity. S-doped graphene blended PHBHHx membrane seems like a suitable patch for biomedical treatments as a hydrophobic membrane where less cell adhesion and proliferation are required like the prevention of peritoneal adhesion.
Keywords: S-doped graphene; PHBHHx; Protein adhesion; Cell attachment; Tissue engineering; PHYSICAL-PROPERTIES; MECHANICAL-PROPERTIES; CYCLIC VOLTAMMETRY; STEM-CELLS; POLY(3-HYDROXYBUTYRATE-CO-3-HYDROXYHEXANOATE); BIOCOMPATIBILITY; PROLIFERATION; SCAFFOLDS; FILMS; Biochemistry & Molecular Biology; Chemistry; Polymer Science